Quiet street : on American privilege - McDonell, Nick, 1984- (Pantheon Books, 2023)
"A bold and moving exploration of the American elite that exposes how the ruling class-even when well-intentioned-perpetuates cycles of wealth, power, and injustice Growing up on New York City's Upper East Side, Nick McDonell was surrounded by luxury-sailing lessons in the Hamptons, school galas at the Met, and holidays on private jets. It was this rarified life that he explored in his early novels, but then left behind as a war correspondent in Iraq and Afghanistan. In Quiet Street, McDonell returns to the sidewalks of his youth, exhuming his own upbringing, and those of his wealthy peers, with bracing honesty. Through summer safaris and winter ski trips, ill-omened handshakes and schoolyard microaggressions, fox-hunting rituals and sexually precocious tweens, McDonell examines the ruling class in painstaking detail, documenting how wealth and power are hoarded, encoded, and passed down from one generation to the next. Crucially, he also demonstrates how outsiders-the poor, the non-white, the suburban-are kept in the dark. Searing and precise yet always deeply human, Quiet Street examines the problem of America's one-percenters, whose vision of a more just world never materializes. Who are these people, how do they hold on to power, and what would it take for them to share it? Quiet Street pursues these questions through the highly personal, but universal, experience of growing up and coming to terms with the culture that made you" --